DEVELOPMENT OF INFANTS’ ANTHROPOMETRIC MEASUREMENTS VIDEO FOR KNOWLEDGE IMPROVEMENT - Andriani, Rini (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2023)
Background: Video is one of learning media that is very useful in explaining various basic clinical skills, infant anthropometric measurements, especially in distance learningLearning Media Review: The video is structured into two parts, namely the provision of short visual material and demonstration of clinical skills in infant anthropometric measurements in audio and visual form. Validation by media experts, material experts, and teaching lecturers stated that video was appropriate for use as a learning media. Small group trials found that video provide knowledge that can be understood by the target audience.Conclusion: Preparation of videos with validation by experts can produce appropriate learning media and increase the target audience's knowledge